Educational design research: Portraying, conducting, and enhancing productive scholarship. Issue 1 (5th August 2020) - McKenney, Susan; Reeves, Thomas C.
Abstract: Context: Solutionism is the all‐too‐common human propensity to jump to a solution before adequately understanding the nature of a problem. Solutionism has long been prevalent in efforts to improve education at all levels, including medical education. Thesis: Educational design research (EDR) is a genre of research that features the gaining of in‐depth understanding of a problem before any prototype solution is designed and tested. It is different from other forms of scientific inquiry because it is committed to the simultaneous development of both theoretical insights and practical solutions, together with stakeholders. This approach is powerful for theory building because it privileges ecologically valid studies that embrace the complexity of investigating learning in authentic (as opposed to laboratory) settings. When conducted well, both the research process and its outcomes generate valuable contributions to practice. Preview: This article constitutes an expository essay on EDR, comprised of three movements. First, the approach is defined, its origins are presented, and its characteristics are described. Second, a generic model for conducting EDR is offered, and illustrated with examples from the field of medical education. Third, pathways towards advancing this form of inquiry are discussed, including ways to address inherent challenges and limitations, as well as recommendations for the medical education community. Although EDR is no panacea, this article illustrates how it can serve medical education research in a wide variety of geographic and disciplinary contexts.